Insulin protects cognitive function in experimental stroke. Issue 10 (October 1990) - Strong, A J; Fairfield, J E; Monteiro, E; Kirby, M; Hogg, A R; Snape, M; Ross-Field, L
Abstract : There is evidence from in vitro systems that the extent of neuronal loss in acute central nervous system ischaemia can be reduced by manoeuvres which restrict availability of glucose to the ischaemic area. Experiments were designed to test whether hypoglycaemia induced with insulin is associated with improved behavioural outcome in a recovery model of stroke. Rats learned a maze task as a test of working memory, believed to be subserved by the hippocampus, and then had a period of cerebral ischaemia, followed by reperfusion. After an interval of 14 days they were tested on the same maze, where lesioned animals had very significant (p less than 0.0001) impairment of working memory, whereas lesioned and treated (2.0 u/kg-1 insulin, minimum single plasma glucose value: 3.1 mmol/l-1) animals were indistinguishable from control animals. It is concluded that a striking degree of protection can be obtained with levels of mild hypoglycaemia which may be acceptable and practicable for use in humans.